Cellular therapy and transplantation
Cellular Therapy and Transplantation is a new international, peer-reviewed, open access journal which publishes articles in the fields of cellular and genetic therapy and transplantation. While the journal is international in scope and publication, one of its aims is to provide a forum for work undertaken by scientists from the former Soviet Union and make it widely accessible.